Epidemiology of road traffic crashes reported in the Kurunegala Police Division in Sri Lanka - P. G. Amarasinghe (Sri Lanka Journal of Medicine, 2019)
Background: Road Traffic Crashes (RTCs) kill 1.24 million people in the world annually. It has become a major but neglected public health problem in the world including Sri Lanka.  Objective: To describe characteristics of RTCs and socio-demographic characteristics of involved road users reported at the Kurunegala Police Division (KPD), Sri Lanka during April to December in 2013.  Materials and Methods: A descriptive cross-sectional study was conducted and the study participants were involved road users of consecutively reported RTCs to ten police stations in the KPD. Data were collected using an interviewer administered structured questionnaire and a data record sheet. Results: 851 RTCs were reported during the study period with 1481 vehicles and 1887 road users involved. 7.8% of the RTCs were fatal, 70% resulted in non-fatal injuries and 22.2% caused damage only. The average rate of RTCs was 03 per day and majority (37.3%) was reported from urban areas between 12.00hr-17.59hrs. Fatal RTCs were higher between 0.00hr-05.59hrs in rural areas. The leading type of vehicles involved were motorcycles and the most vulnerable road users were males (84%) between 31- 40 years. The majority of motorcyclists and pillion riders (82.8%) were wearing a helmet at the time of the crash. The majority of pedestrians (85.2%) were injured while crossing the road, out of which 34% were on a pedestrian crossing.  Conclusion: Young males in productive age were the most affected by RTCs.